2002
DOI: 10.1002/ajmg.a.10038
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of isolated femoral bent bone skeletal dysplasia: Problems in differential diagnosis and genetic counseling

Abstract: Severe localized and symmetric bowing of the femora, in the absence of other significant skeletal or nonskeletal abnormalities, is a rare prenatal ultrasound finding. A 38-year-old woman was referred at 19 weeks gestation and ultrasound of the fetus showed severe shortening, and marked symmetric bowing of the femora. A provisional diagnosis of kyphomelic dysplasia (KD) was made. The patient elected termination of pregnancy and post mortem assessments were most consistent with kyphomelic dysplasia. KD is bent-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 31 publications
(41 reference statements)
1
14
0
1
Order By: Relevance
“…In the Revised International Nosology and Classification of Genetic Disorders of Bone—200612, SWS has been classified under the bent skeletal dysplasias along with campomelic dysplasia (CMPD), Cumming syndrome and kyphomelic dysplasia17. Alternative diagnostic considerations in the setting of bowed femora and mild‐to‐moderate micromelia would be Antley–Bixler syndrome, femoral hypoplasia‐unusual facies syndrome (FH‐UFS), osteogenesis imperfecta (OI) and diastrophic dysplasia18–21. They can be diagnosed easily at birth based on clinical and radiological findings.…”
Section: Discussionmentioning
confidence: 99%
“…In the Revised International Nosology and Classification of Genetic Disorders of Bone—200612, SWS has been classified under the bent skeletal dysplasias along with campomelic dysplasia (CMPD), Cumming syndrome and kyphomelic dysplasia17. Alternative diagnostic considerations in the setting of bowed femora and mild‐to‐moderate micromelia would be Antley–Bixler syndrome, femoral hypoplasia‐unusual facies syndrome (FH‐UFS), osteogenesis imperfecta (OI) and diastrophic dysplasia18–21. They can be diagnosed easily at birth based on clinical and radiological findings.…”
Section: Discussionmentioning
confidence: 99%
“…In another report, investigators found 40% of cases to be false-positive for the detection of isolated clubfoot, all of which were diagnosed in the third trimester of pregnancy (5). Yet a third report described the difficulty in distinguishing between isolated bowed femurs and true dysplasia, making parental counseling a challenge (6).…”
Section: The Practicementioning
confidence: 97%
“…The closest nosological presentations are Antley-Bixler syndrome, which can show a sex reversal, and kyphomelic dysplasia [6,18] . The Stüve-Wiedemann and Cumming syndrome which belong to the same group in The International Nosology and Classification of Constitutional Disorder of Bones also belong to the differential diagnosis ( table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Short first metacarpals or short second phalanges are sometimes observed. Other signs are less common such as the absence of one pair of ribs, vertebral ossification defects, clavicular hypoplasia and absence of olfactory bulbs and tracts [1,[5][6][7] . Crania facial dysmorphism includes macrocephaly, low-set ears, hypertelorism, long philtrum, micrognathia, flat facies and cleft palate [8] .…”
Section: Introductionmentioning
confidence: 99%